Improved Multi Service-Reverse Charging Models for the Multi Link Internet wireless Using QOS Bit Error Rate QoS Attribute - Fitri Maya Puspita; Evi Yuliza; Weny Herlina; Yunita Yunita; Rohania Rohania (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2020)
n this article, a multi-link internet reverse charging scheme model on a multi-service network isproposed. The previous research seldom discussed the reverse charging scheme on multi linkand multi service network. This pricing scheme is designed with the aim of maximizing serviceprovider profits. Basic costs and the level of service satisfaction provided by the ISP is focusedon this attempt. This optimization problem can be solved using LINGO 13.0 software. Thisproblem was made and was divided into several cases. Thus, the results obtained can be aconsideration for ISPs in determining the price of services that can support an ISP. The improvedmodels that produce the maximum solution is case 3 (α and β as variables) and case 4 (α asvariables and β as parameters).